Reconstruction of bilateral tibial aplasia and split hand-foot syndrome in a father and daughter - Ali Al Kaissi; Rudolf Ganger; Klaus Klaushofer; Franz Grill (Wolters Kluwer Medknow Publications, 2014)
Background: Tibial aplasia is of heterogeneous aetiology, the majority of reports are sporadic. We describe the reconstruction procedures in two subjects - a daughter and father manifested autosomal dominant (AD) inheritance of the bilateral tibial aplasia and split hand-foot syndrome. Materials and Methods: Reconstruction of these patients required multiple surgical procedures and orthoprosthesis was mandatory. The main goal of treatment was to achieve walking. Stabilization of the ankle joint by fibular-talar-chondrodesis on both sides, followed by bilateral Brown-procedure at the knee joint level has been applied accordingly. Results: The outcome was with improved function of the deformed limbs and walking was achieved with simultaneous designation of orthotic fitting. Conclusion: This is the first study encompassing the diagnosis and management of a father and daughter with bilateral tibial aplasia associated with variable split hand/foot deformity without foot ablation. Our patients showed the typical AD pattern of inheritance of split-hand/foot and tibial aplasia.